17. Serial peripheral nerve ultrasound in Guillain–Barré syndrome. Issue 3 (March 2016) - Omaira Razali, Siti Nur; Arumugam, Thaarani; Yuki, Nobuhiro; Rozalli, Faizatul Izza; Goh, Khean-Jin; Shahrizaila, Nortina
Abstract : Objective: To assess the longitudinal changes of nerve ultrasound in Guillain–Barré syndrome (GBS) patients. Methods: We prospectively recruited 17 GBS patients and 17 age and gender-matched controls. Serial studies of their nerve conduction parameters and nerve ultrasound, documenting the cross-sectional areas (CSA), were performed at admission and repeated at several time points throughout disease course. Results: Serial nerve ultrasound revealed significantly enlarged CSA in median, ulnar and sural nerves within the first 3 weeks of disease onset. Longitudinal evaluation revealed an improvement in the nerve CSA with time, reaching significance in the ulnar and sural nerves after 12 weeks. There was no significant difference between the demyelinating and axonal subtypes. There was also no significant correlation found between nerve CSA and neurophysiological parameters or changes in nerve CSA and muscle strength. Conclusion: In GBS, serial studies of peripheral nerve ultrasound CSA are helpful to detect a gradual improvement in the nerve size.